A review of the effects of light-emitting diodes (LEDs) on the growth of sunflower microgreens and their nutritional potential - Hong, Lim Chew; Sreeramanan Subramaniam, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sunflower (Helianthus annuus) microgreens have become known as a potent source of essential nutrients and bioactive compounds with numerous health benefits. The microgreens industry has traditionally favored popular microgreens from the Brassicaceae family such as kale, rocket, and broccoli. Sunflower microgreens are characterized by their richness in vitamins, minerals, antioxidants, and phytochemicals that contribute significantly to a nutritious diet. However, their nutrient content can be influenced by various factors, including growing conditions and lighting. Light-emitting diodes (LEDs) offer precise control of light spectrum, light intensity, and lighting duration, enabling customized lighting systems optimized for growing sunflower microgreens. Pre-treatment and optimal harvest timing affect the quality and yield of microgreens, and sunflower microgreens are no exception. Accordingly, sunflower microgreens are typically harvested within 7 days of cultivation, making them ideal for mass production. The use of LED technology in the cultivation of microgreens offers the opportunity to further enhance their nutritional value and therapeutic potential. This review provides an overview of the benefits of sunflowers, sunflower microgreens, pre-treatments, and the ideal harvest period. The potential improvements from LED lighting are discussed and its impact on human health is explained.